2019
DOI: 10.1002/pa.2038
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the causes of road traffic accidents in India: An empirical investigation

Abstract: This study utilizes data for the period 2006–2015 to estimate the determinants of road fatality rates in the Indian states. We employ baseline regression, where the total traffic fatalities, total traffic injuries, rural road fatalities, and urban road fatalities are the functions of human errors in driving, weather conditions, and some control variables. This paper is exclusively focussed upon different sets of human‐driven factors in influencing the road fatality across the Indian states. Our empirical resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 17 publications
7
10
0
Order By: Relevance
“…This corroborates the findings from the WHO Global status report on alcohol and health, which reported increased instances of crashes under the influence of alcohol among young drivers due to weekend get-togethers [1]. Additionally, it is also in alignment with the MoRTH annual report (2019) [5] and with some previous studies [11,24].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This corroborates the findings from the WHO Global status report on alcohol and health, which reported increased instances of crashes under the influence of alcohol among young drivers due to weekend get-togethers [1]. Additionally, it is also in alignment with the MoRTH annual report (2019) [5] and with some previous studies [11,24].…”
Section: Discussionsupporting
confidence: 90%
“…For the next major cause of fatal crash, i.e., driving under the influence of alcohol, the analysis revealed that it contributes to almost one-fifth of the total fatal crashes. This is in alignment with the MoRTH annual report (2019) [5] and with some previous studies [24]. Here, it should be noted that in addition to driving under the influence of alcohol, the role of other factors such as vehicle and environment should also be given importance in future investigations.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations